2018
DOI: 10.1136/bmjopen-2017-016674
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a nurse-supported self-management programme for dual sensory impaired older adults in long-term care: a cluster randomised controlled trial

Abstract: ObjectiveTo evaluate the effectiveness of a nurse-supported self-management programme to improve social participation of dual sensory impaired older adults in long-term care homes.DesignCluster randomised controlled trial.SettingThirty long-term care homes across the Netherlands.ParticipantsLong-term care homes were randomised into intervention clusters (n=17) and control clusters (n=13), involving 89 dual sensory impaired older adults and 56 licensed practical nurses.InterventionNurse-supported self-managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The results are in line, however, with other studies on interventions for older adults with vision and/or hearing loss. Two recent studies on integrated care for older adults with DSL showed no difference in hearing handicap or quality of life (McMahon et al, 2017) and only on one (instrumental activities of daily living) of four domains of social participation (Roets-Merken et al, 2018). In addition, a meta-analysis of eight interventions for older adults with vision or hearing loss revealed no significant effects in favor of interventions on quality of life or daily functioning (Roets-Merken et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The results are in line, however, with other studies on interventions for older adults with vision and/or hearing loss. Two recent studies on integrated care for older adults with DSL showed no difference in hearing handicap or quality of life (McMahon et al, 2017) and only on one (instrumental activities of daily living) of four domains of social participation (Roets-Merken et al, 2018). In addition, a meta-analysis of eight interventions for older adults with vision or hearing loss revealed no significant effects in favor of interventions on quality of life or daily functioning (Roets-Merken et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…There are a few initiatives reported in the literature to integrate healthcare for older adults with DSL (McMahon et al, 2017;Roets-Merken et al, 2018). McMahon et al (2017) performed an audiological screening of older adults with low vision and provided education and rehabilitation to those with hearing loss who did not own or did not regularly use hearing aids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies aimed to increase knowledge in staff using methods such as educational videotapes [ 11 ], workshops [ 12 ], or by attaching instructions about insertion and maintenance of hearing aids to the inside of residents’ wardrobes [ 13 ]. Training residents to manage their own devices has also been applied in one identified study [ 14 ]. Whilst these practices were reportedly beneficial in increasing staff and residents’ knowledge, how and why these have been effective is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies aimed to increase knowledge in staff using methods such as educational videotapes (11), workshops (12), or by attaching instructions about insertion and maintenance of hearing aids to the inside of residents' wardrobes (13). Training residents to manage their own devices has also been applied in one identi ed study (14). Whilst these practices were reportedly bene cial in increasing staff and residents' knowledge, how and why these have been effective is largely unknown.…”
Section: Introductionmentioning
confidence: 99%